2022
DOI: 10.1039/d2qo00008c
|View full text |Cite
|
Sign up to set email alerts
|

Selective synthesis and reactivity expansion of α,β-unsaturated geminal diazides

Abstract: α,β-Unsaturated gem-diazides were selectively obtained catalyzed by Yb(TfO)3 using α,β-unsaturated aldehydes as substrates and TMSN3 as a nitrogen source under mild and simple conditions in moderate yields without Schmidt and allylic rearrangement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Due to there being a range of available methods, geminal diazides derived from aldehydes are broadly accessible. 81 82 83 While studies on the reactivity of such diazides are still rare, a few interesting reactions with diazides derived from α,β-unsaturated aldehydes were recently disclosed. As summarized in Scheme 41 , the diazide 83 behaves mostly like a synthetic equivalent of a N , N -acetal: Single and double substitution is possible, as is elimination to imines and oxidation to nitriles.…”
Section: Reactivities Of Geminal Diazidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to there being a range of available methods, geminal diazides derived from aldehydes are broadly accessible. 81 82 83 While studies on the reactivity of such diazides are still rare, a few interesting reactions with diazides derived from α,β-unsaturated aldehydes were recently disclosed. As summarized in Scheme 41 , the diazide 83 behaves mostly like a synthetic equivalent of a N , N -acetal: Single and double substitution is possible, as is elimination to imines and oxidation to nitriles.…”
Section: Reactivities Of Geminal Diazidesmentioning
confidence: 99%
“…He and co-workers have studied the reactivity of geminal diazides with the diazido group at an allylic position. 83 It was shown that double substitution was possible in the presence of Cu(OTf) 2 as a Lewis acid catalyst (Scheme 44 ). Diazides 94 reacted with an excess of electron-rich pyrroles (or furans) to give the bis(heterocyclo)methylene derivatives 95 .…”
Section: Reactivities Of Geminal Diazidesmentioning
confidence: 99%